Measuring the bat-ball impact location from bat acceleration - Lyu, B.; Smith, L. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2025)
This study describes a novel method to identify the bat-ball impact location from accelerations measured at the bat knob. The magnitude of mode 1 and mode 2 accelerations were normalized by the swing speed and found as a function of the impact location. The impact location was identified by minimizing the error of normalized acceleration from impacts of batters swinging at different speeds. Impact locations from the accelerations were then compared with locations measured by high-speed video. Good agreement was found for bats with an asymmetric acceleration signature.